Reforming the Financial Mechanism of Public Non-Business Units in Vietnam: Research in Lao Cai Province - Khanh, Vo Thi Van; Huong, Nguyen Thi Thu (Business and Economic Research, 2021)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The content of the administrative reform plan for the period 2011–2020 of the Government of Vietnam on the basis of the overall reform of the national administration, focuses on four main areas, namely institutional reform and organizational reform. structure, building and developing contingent of civil servants and public finance (Government, 2011). Thus, along with the institutional and organizational reform, the public finance reform is also a central task of the administrative reform in the condition that Vietnam continues to strongly transition from the centralized mechanism. The subsidy to a socialist-oriented market economy, in particular, is even more necessary when Vietnam has become an official member of the World Trade Organization. One of the current concerns for good implementation of public finance reform is the implementation of autonomy and self-responsibility for the use of payroll and administrative management funding for administrative agencies. state and financial autonomy mechanism for non-business units. This article focuses on analyzing the current situation of reforming the financial operation mechanism of public non-business units in Lao Cai province, Vietnam, pointing out the achievements, limitations, causes and some recommendations to end. promote the reform of the financial operation mechanism of public non-business units in Lao Cai province, Vietnam in the context of world economic integration.